Analisis SWOT Dalam Penghimpunan Zakat Pada Generasi Milenial - Wardy Putra, Trisno; Nasri Katman, Muh.; Syathir Sofyan, Andi (INSTITUT AGAMA ISLAM TARBIYATUT THOLABAH LAMONGAN, INDONESIA, 2021)
This study aims to explain the collection of zakat in the millennial generation. Based on the 2020 population census, the millennial generation population reached 69.38 million people or about 25.87% of the total population of Indonesia. The research method used is the SWOT (Strength, Weaknesses, Opportunities, Threats) analysis method with the main objective of knowing the situation comprehensively. Based on the research assumptions, the potential for millennial zakat is very large. As for the SWOT analysis of the millennial generation zakat collection, it is necessary to strengthen zakat literacy, Islamic studies, and counseling. In addition, government support and parental example are also one of the supporting factors in increasing millennial zakat collection.